Selection of a Burner for Combustion of Low Calorific Process Gases. Issue 13 (3rd October 2021) - Kolczyk, E.
ABSTRACT: Using the numerical method, various constructions of burners for combustion of low calorific process gas were analyzed. For the burners, in a coaxial system of pipes in which the process gas was fed in the inner tube, a larger number of products was obtained 0.98 and higher temperatures 995°C. The most advantageous solution was the burner in the construction of parallel slots to which utilities with different speeds were supplied. A maximum temperature of 1046°C and 0.997 of products was obtained for this type of burner. Because process gas is a lean fuel, it is enriched with natural gas. Therefore, the next step was to select a burner that burns the process gas with natural gas. For the initial mixing and burning of the process gas mixture with natural gas, the maximum temperature was 1269°C and obtained 0.93 of products. In the system, when the natural gas burner was below the process gas burner, the maximum temperature was 1088°C and 0.996 of the products.The best constructional solution was the system when the natural gas burner is located above the process gas burner. It provides a maximum temperature of 1288°C in the upper space of the combustion chamber and 0.995 of products.